Rationing and Value Theory - Makower, H. (Review of Economic Studies, 1945)
Journal Article Rationing and Value Theory Get access H. Makower H. Makower Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 13, Issue 2, 1945, Pages 75–80, https://doi.org/10.2307/2296038 Published: 01 September 1945